2010
DOI: 10.1158/1078-0432.ccr-09-3136
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-Testis Antigens and Immunosurveillance in Human Cutaneous Squamous Cell and Basal Cell Carcinomas

Abstract: Purpose: Nonmelanoma skin cancer is the most common cancer and comprises basal cell carcinoma (BCC) and squamous cell carcinoma (SCC). The incidence of SCC increases drastically in immunosuppressed individuals, suggesting a critical role of the immune system in controlling SCC. To find an explanation for the selective immunosurveillance of SCC, we investigated the expression of cancer-testis (CT) antigens and MHC class I (MHC-I) and the infiltration by immune cells in BCC and SCC.Experimental Design: We determ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
83
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 56 publications
(91 citation statements)
references
References 31 publications
4
83
1
3
Order By: Relevance
“…Most tumors expressed more than one TAA, which has been described for other tumor entities (16)(17)(18), and which enables therapeutic-targeting of multiple antigens at the same time.…”
Section: Discussionmentioning
confidence: 98%
“…Most tumors expressed more than one TAA, which has been described for other tumor entities (16)(17)(18), and which enables therapeutic-targeting of multiple antigens at the same time.…”
Section: Discussionmentioning
confidence: 98%
“…Although these are limited in number, our data suggest that these changes in the immune environment may be crucial for tumor control and highlight the poorly understood interface between targeted therapy and immune responses. BCCs frequently express multiple cancer testis antigens, but are also associated with relative absence of MHC class I molecules from tumor cells, and it has been hypothesized that BCCs produce immunosuppressive factors such as IL10 (2,21) and therefore are resistant to adaptive immune response. This might explain the absence of infiltrating CD8 þ cells in BCC.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the presence of cancer testis and other tumor antigens, BCCs escape from immune surveillance by the downregulation of HLA class I expression (2). Recently, targeted therapy based on knowledge of BCC pathogenesis has become available either commercially or in the context of human clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was shown that Aldara treatment resulted in pDC-mediated tumour killing in a murine melanoma model 7 . We and others previously showed that treatment with IMQ and Aldara resulted in upregulation of MHC class I on tumour cells, recruitment of T cells into the tumour, enhancement of their effector function and mobilization of Langerhans cells and inflammatory DCs, as well as in interleukin (IL)-17 production by dermal gd-T cells 8,[9][10][11][12] .…”
mentioning
confidence: 99%